What is the cost, impact, and willingness to pay for an Amputee Peer Support Program?. Issue 2 (5th April 2023) - Brusco, Natasha K.; Foster, Sarah; Noonan, Melissa; Waugh, Fiona; Warren, Narelle
Abstract : Background: The provision of peer support from those who have already made positive adjustments to amputation is recommended for people incurring a major limb amputation; however, few receive this service. Objective: From a program perspective, determine the cost, impact, and willingness to pay for an Amputee Peer Support Program. Study design: Cost analysis. Methods: Cost of the Amputee Peer Support Program included a cost analysis of program data over a 5-year time horizon (2013–2018) reported in Australian Dollars 2018/2019. Impact and willingness to pay for an Amputee Peer Support Program was determined through surveys of the 3 participant groups: referring health professionals, program volunteers, and program participants. Results: Over 5 years, there were 793 program participants, serviced by 256 program volunteers, for a cost of 631, 497. The cost per program participant was 796. Thirty-eight health professionals, 86 program volunteers, and 12 program participants reported on impact and willingness to pay. The Program was reported to have a positive impact on all participant groups. The themes of access to resources and information and the provision of social and emotional well-being were identified across all 3 groups as being important. All 3 groups reported a higher willingness to pay for the health service (range 113–450), National Disability Insurance Scheme (156–432), and private health insurance (153–347), and a lower willingness to pay for the program participant (23–49). Conclusion: Amputee peer support had a positive impact on those receiving and providing the service. Amputee peer support is likely to be a powerful yet inexpensive addition to routine care.